Comparative genomics of Coniophora olivacea reveals different patterns of genome expansion in Boletales - Raúl Castanera; Gúmer Pérez; Leticia López-Varas; Joëlle Amselem; Kurt LaButti; Vasanth Singan; Anna Lipzen; Sajeet Haridas; Kerrie Barry; Igor V. Grigoriev; Antonio G. Pisabarro; Lucía Ramírez (BMC Genomics, 2017)
Abstract Background Coniophora olivacea is a basidiomycete fungus belonging to the order Boletales that produces brown-rot decay on dead wood of conifers. The Boletales order comprises a diverse group of species including saprotrophs and ectomycorrhizal fungi that show important differences in genome size. Results In this study we report the 39.07-megabase (Mb) draft genome assembly and annotation of C. olivacea. A total of 14,928 genes were annotated, including 470 putatively secreted proteins enriched in functions involved in lignocellulose degradation. Using similarity clustering and protein structure prediction we identified a new family of 10 putative lytic polysaccharide monooxygenase genes. This family is conserved in basidiomycota and lacks of previous functional annotation. Further analyses showed that C. olivacea has a low repetitive genome, with 2.91% of repeats and a restrained content of transposable elements (TEs). The annotation of TEs in four related Boletales yielded important differences in repeat content, ranging from 3.94 to 41.17% of the genome size. The distribution of insertion ages of LTR-retrotransposons showed that differential expansions of these repetitive elements have shaped the genome architecture of Boletales over the last 60 million years. Conclusions Coniophora olivacea has a small, compact genome that shows macrosynteny with Coniophora puteana. The functional annotation revealed the enzymatic signature of a canonical brown-rot. The annotation and comparative genomics of transposable elements uncovered their particular contraction in the Coniophora genera, highlighting their role in the differential genome expansions found in Boletales species.